Novel D-pi-A Organic Dyes with Thieno[3,2-b]thiophene-3,4-ethylenedioxythiophene Unit as a pi-Bridge for Highly Efficient Dye-Sensitized Solar Cells with Long-Term Stability - Lee, Min-Woo; Kim, Jae-Yup; Lee, Duck-Hyung; Ko, Min Jae (American Chemical Society, 2014)
This paper reports on new D-pi-A organic dyes for application in dye-sensitized solar cells (DSSCs), which were developed by incorporating thieno[3,2-b]thiophene-thiophene (M9) and thieno[3,2-b]thiophene-EDOT (M10) as pi-bridges. These dyes exhibited relatively small highest occupied molecular orbital (HOMO)-lowest unoccupied molecular orbital (LUMO) energy gaps in spite of the short pi-conjugation lengths, resulting in broad spectral responses. As photosensitizers in DSSCs, M10 showed a broader spectral response than M9, leading to a greater short-circuit photocurrent (J(sc)). In addition, M10 exhibited higher open-circuit voltage (V-oc) compared to M9, because of the greater electron lifetime of the photoanode. The impedance analysis revealed that the greater electron lifetime of the photoanode with M10 was attributed to the lower electron recombination rate caused by the blocking effect of the bulky EDOT unit. As a result, M10 showed much higher conversion efficiency (eta = 7.00%) than M9 (eta = 5.67%) under one sun condition (AM 1.5 G, 100 mW/cm(2)). This conversion efficiency was comparable to that of the conventional Ru-based dye N719 (eta = 7.24%) under the same condition. In addition, M10 exhibited a remarkable long-term stability, i.e., 95% of the initial conversion efficiency was maintained after light soaking for 45 days (1080 h).
Keywords: CHARGE-TRANSFER; ELECTROLYTE